Interest Group Politics and the Licensing of Public Accountants. - Young, S. David (The Accounting Review, 1991)
Abstract Explains why some states in the United States have adopted relatively permissive licensing laws for public accountants. Use of hypotheses to test the power of interest groups, political systems and socioeconomic variables in explaining differences in licensing requirements; Role of the American Institute of Certified Public Accountants.